Free-Standing Black Phosphorus Foils for Energy Storage and Catalysis - Wu, Bing; Kovalska, Evgeniya; Luxa, Jan; Marvan, Petr; Cintl, Štěpán; Sofer, Zdenek (Chemistry (Weinheim an der Bergstrasse, Germany), 2020)
Few-layered black phosphorus (BP) is a two-dimensional material that has attracted intensive attention for applications in energy storage and catalysis due to its large surface area and good electrical and thermal conductivity. Herein, a comparable study of BP electrochemical exfoliation in various solutions of tetrabutylammonium salts (TBAX; X is PF6 - , BF4 - , and ClO4 - ) in DMSO is reported. Based on morphological and structural analyses, it is shown that TBAPF6 /DMSO medium was specifically appropriate for the production of high-quality BP nanosheets with micrometer lateral size and a thickness of about 2.4 nm. TBAPF6 /DMSO-processed, few-layered BP exhibits enhanced hydrogen evolution reaction (HER) catalytic activity compared with that of samples exfoliated with the assistance of BF4 - and ClO4 - ions. Finally, the fabrication of flexible, free-standing BP films and their performance in an all-solid-state supercapacitor device are demonstrated.
Keywords: energy storage; all-solid-state supercapacitors; free-standing films; electrochemistry; black phosphorus